Incorporation of probiotic bacteria on larval culture of Macrobrachium amazonicum (Heller, 1862) (Research, Society and Development, 2021)
In this study, we evaluated the utilization of two probiotics incorporated into the water and in the diet in a larval culture system of Amazon River prawn. Autochthonous probiotic bacteria from the gut of wild juveniles of M. amazonicum juveniles and a commercial probiotic were tested and the following parameters were analyzed: survival, productivity, fresh weight, length, larval condition index (LCI) and larval stage index (LSI). The colonization of the larval gastrointestinal tract by probiotics took place when they were incorporated into diet, while probiotics in the water proved to be unsuccessful. The use of lactic acid bacteria had no significant effects (p>0.05) on survival, productivity, length, fresh weight, LSI and LCI, showing similar results in relation to the control group. However, we recommend the inclusion of probiotics into diet in larval culture of Amazon prawn since this method allowed bacterial gut colonization, which is important to evaluate the resistance to disease in further studies.